Oil organogel system for magnetorheological fluid. Issue 114 (2nd December 2016) - Yang, Jianjian; Yan, Hua; Zhang, Hansong; Wang, Xuemei
Abstract : A new approach to dispersing magnetic particles via an oil organogel formed by a low molecular weight gelator to prepare MRF. Abstract : We introduce a model colloid system comprised of carbonyl iron particles dispersed in oil organogel. The rheological properties of magnetorheological fluids with different particle concentrations were investigated. It was found that the system showed behavior expected from a structured material due to the network of the matrix. The microstructural changes investigated in hysteresis and thixotropic tests demonstrated a compacted chain structure can be obtained by proper shearing. The field-induced shear stress and dynamic modulus proved a promising magnetorheological performance of the suspension.